PERILAKU BALOK PRATEGANG PARSIAL. DENGAN SISTEM PRATARIK YANG MENERIMA BEBAN MONOTONI - Liliana
This research deals with a study of the shear failure mechanism for both original and repaired pre-tensioning concrete beams. Ten specimens with aspect ratio a/d=3 in concrete compressive strength of 30 AMPa, 60 MPa, 70 MPa,, with partial prestressing ratio of 60% and 100% were tested under monotonic three point flexural loading condition. Nine of the specimens are original and the rest one was repaired by grouting the crack area with polymer matrix. The test results show that the cross section ductility of the normal strength beams without shear reinforcement is less than 4, but is equal to 4 for the high strength beam. The cross section and structure ductility increased more than 4 for the beam specimen with shear reinforcement. This indicates that shear reinforcement beams behave more ductile it means the beam they can resist the flexural deformation. The test results analysis were compared with the shear capacity stated in Indonesian code SK-SNI T-15-1991-03. It indicates that the values found from Indonesian code SK-SNI T-I5-1991-03 is conservative for the specimen beams without shear reinforcement. This is valid for both normal and high strength beam specimens. For the specimen with shear reinforcement, the shear capacity found from test results analysis similar to that found from the code's formula. The crack patterns for the normal and high strength beams without shear reinforcement the flexural cracks tended to develop shear cracks and failed under a bending shear failure mode. For the normal specimen beams with shear reinforcement, flexural crack pattern occured, but for the high strength concrete, bending shear mode was developed to be the failure mechanism. For the repaired beams, bending shear failure mechanism started with bond stress loss near the supports. Although the specimen could carry 79.46% from the total load capacity, the specimen failed more brittle comparing with the original beams did. Consideration should be applied in case of shear strength design of beam based on SK-SNI T-15-1991-03 using high strength concrete.